The Characteristic of Egg Replacer from Soy Protein Isolate, Whey Protein Isolate, Corn Starch, Potato Starch, Guar Gum, and Xanthan Gum - Juni Ario; Elisa Julianti; Era Yusraini (Jurnal Rekayasa Pangan dan Pertanian, 2015)
The research was aimed to study the physicochemical and functional characterization of egg replacer from soy protein isolate, whey protein isolate, corn starch, potato starch, guar gum, and xanthan gum. The research had been performed using factorial completely randomized design, with one factor i.e the ratio of: soy protein isolate, whey protein isolate, corn starch, potato starch, guar gum, and xanthan gum (E): 62,5%:0%:18,75%:18,125%:0,625%:0% (E1); (62,5%:0%:18,75%:17,5%:1,25%:0% (E2); 62,5%:0%:18,75%:16,875%:1,875%:0% (E3); 62,5%:0%:18,75%:18,125%:0%:0,625% (E4); 62,5%:0%:18,75%:17,5%:0%:1,25% (E5); 62,5%:0%;18,75%:16,875%:0%:1,875% (E6); 0%:62,5%:18,75%:18,125%:0,625%:0% (E7); 0%:62,5%:18,75%:17,5%:1,25%:0% (E8); 0%:62,5%;18,75%:16,875%:1,875%:0% (E9); 0%:62,5%:18,75%:18,125%:0%: 0,625% (E10); 0%:62,5%:18,75%:17,5%:0%:1,25% (E11); 0%:62,5%;18,75%:16,875%:0%: 1,875% (E12). Parameters analyzed were color, bulk density, moisture content, ash content, fat content, protein content, carbohydrate content, foaming capacity, foaming stability, emulsion activity, and emulsion stability.        The research showed that the ratio of soy protein isolate, whey protein isolate, corn starch, potato starch, guar gum, and xanthan gum had highly significant effect (p<0,01) on all parameters except moisture content. The research showed that the ratio of soy protein isolate, whey protein isolate, corn starch, potato starch, guar gum, and xanthan gum was significantly different (p<0,01) with physicochemical and functional characterization  with physicochemical and functional characterization of control (egg flour). Ratio at E12 (0%:62,5%;18,75%:16,875%:0%:1,875%) had the characteristics that almost resembles to egg flour, so it could be used as a egg replacer on egg-based products such as bread and cake. Keyword: Egg flour, egg replacer, gum, protein isolate, starch